Does it work? Assessing the pragmatic validity of educational interventions: Empirical evidence and construct validation from the Indian academic sector - Naqvi, Ariz; Momin, Mujtaba; Said, Dina (Edelweiss Applied Science and Technology, 2025)
This research examines the pragmatic validity of educational interventions by developing a Personal Effectiveness Scale (PES) for university instructors in India and focusing on four constructs that are represented in Self-efficacy (SE), Time-Use Efficiency (TUE), Innovative Work Behavior (IWB), and Transformative Leadership (TL). The authors collected a sample of 300 university teachers across 27 universities. The construct was validated by implementing Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Also, Structural Equation Modeling (SEM) revealed that PES significantly predicts job satisfaction and teaching effectiveness, explaining 19% and 17.4% of the variance, respectively. IWB demonstrated the most substantial impact on job satisfaction (0.3527), while TUE was the most influential in teaching effectiveness (0.2598). The findings highlight critical areas such as mentorship deficiencies, high student-teacher ratios, and inadequate institutional support. The study provides a robust tool for assessing faculty effectiveness, contributing to ongoing efforts to improve the quality of higher education in India. Additionally, the research suggests improving professional development opportunities and implementing innovative teaching strategies to enhance academic performance. Future research should explore the PES scale’s cross-cultural applicability and institutional factors affecting personal effectiveness.